(untitled) (European Journal of Pure and Applied Mathematics, 2021)
TheÂ purpose of this paper is toÂ define and studyÂ a newÂ class of sets called microÂ generalizedÂ closed sets and defineÂ micro generalized continuous function and irresolute micro generalized continuous functionÂ in micro topological spaces. Basic properties of micro generalized closed setsÂ and its characterizations are analyzed.